(3JNQjL GdOdGdGJ GdSeYjI Ydi eG cGf aj YgO QShd Gddg Udi Gddg Ydjg hSde ef GdMQa hGdUfGFY hGdYeGdGJ GdTQYjIs - (3CHh GdMSf Ydj Hf eMeO Hf CMeO Hf ehSi Hf eSYhO Hf CHi ZaQI GdNRGYi GHf Pi GdhRGQJjfs; (3GHf XgjQI , eMeO Hf eMeO Hf CHj HcQ Hf Ydj Gdecj GdeNRhej, LeGd GdOjf,J (B986 (3g` s
(3ChdgG (B:s
(3JJab ai ChdgG eY Chd GdfSNI GdChdi s
(3BNQgG (B:s
(3hjJab BNQgG eY BNQ GdLRA GdKGfi ef GdfSNI GdKGfjI s
(3HgG VHWs
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
Keywords: (3GdJGQjNs